Fraseologien i forgrunnen — fraseologisk register som ledd i ordbokens tilgangsstruktur - Jónsson, Jón Hilmar (Nordiske Studier i Leksikografi, 2003)
Most dictionaries contain a multitude of phrases. The choice of entry within which a phrase is placed is often arbitrary, which can cause problems both for the lexicographer and the user. Giving phrases independent status in the list of headwords does give the user direct access to them, but this type of approach is only suitable for a limited number of the phrases which need to be included in a general language dictionary. I n phrasal dictionaries the question of access to the material becomes even more acute. The importance of structural patterns in the phrases can be made use of in the ordering and sorting of the phrases, giving the user a more cohesive view of the data. A structured index of the phrases in the dictionary is of great value in this context, especially in an onomasiological dictionary, where the entries are based on semantic criteria. In the making of such an index, the lexicographer must evaluate different approaches in the classification and alphabetization of the material. The topic of this paper is the role of such an index of all the phrases contained in an onomasiological dictionary now in preparation for Icelandic.